Influence of GnRH treatment on service period in buffaloes - DUGWEKAR, Y G; SARVAIYA, N P; SUTHAR, B N; SHAH, R M; CHAUDHARY, C F; BRAHMKSHTRI, K G; DERASHRI, H J (The Indian Journal of Animal Reproduction, 2023)
Studies were conducted on 50 post-partum Mehsani buffaloes. Twenty nine buffaloes received 5.0 ml Receptal(Buserelin acetate 0.0042 mg/ml) i.m. on day 20, post-partum (Gr. I), 14 buffaloes received the same dose ofReceptal on day45 post-partum(Gr. II) and 7 animals served as untreated control (Gr. III). Eleven and 3 animals responded to the GnRHtreatment in Gr. I and II, respectively, and 8 and 2 animals in the respective groups conceived with an average service periodof 43 and 55 days. Five out of 7 animals conceived by day 82 post-partum in the control group. The service period (82 days)in the control group was considerably higher as compared to both the treatment groups. In the second experiment, 20 postpartumbuffaloes were treated with 5 ml. Receptal on day 35 post-partum. Further, these animals received 5 ml Iliren (PGF p)on day 45 post- partum and a second dose of 5.0 ml. Receptal on the day of estrus and were inseminated with good qualitysemen. Only two out often control animals became pregnant to first service with a service period of 53 days. In the treatmentgroup 12 animals responded to estrus, of which 9 became pregnant (based on progesterone assay on day 21 post breeding).However, subsequently, on clinical examination at day 60 post-breeding, only 6 animals were found to be pregnant and theremaining 3 animals had early embryonic mortality between day 21 and day 60 post-breeding. The service period in the treatedanimals was 50 days. Serum estradiol and progesterone levels were useful in the detection of pregnant, non-pregnant and earlyembryonic mortality cases.
Keywords: GnRH treatment; inter-calving period; buffaloes